Consistency in the histological diagnosis of epithelial abnormalities of the cervix uteri. Issue 1 (January 1968) - Cocker, J.; Fox, H.; Langley, F. A.
Abstract : A group of pathologists, all working in the same laboratory and all applying the same diagnostic criteria to the diagnosis of epithelial abnormalities in the uterine cervix, have studied the consistency with which they have applied these criteria. Epithelial abnormalities were ranked, and a series of sections were diagnosed separately by each pathologist at various times over a number of years. Both consistency and trend were studied by a graphed statistical method and it was shown that not only were there serious inconsistencies in diagnosis between the various pathologists but also between the diagnoses made by individual pathologists studying the same section at various times. It is suggested that this inconsistency in the application of agreed diagnostic criteria is of importance when considering discrepancies between reported series of cervical epithelial abnormalities and that the type of study described is of value in assessing both variations in diagnostic criteria between different laboratories and the consistency of pathologists in training. Any slight change in the application of diagnostic criteria for any individual pathologist with the passage of time may also be detected by this technique.